The Development of e-Worksheet based on High Order Thinking Skills (HOTS) for Critical Thinking Student - Hartono, Jessica Kristanti; Nur'aini M, Rida Sitri; Fauzia, Izza; Juliani, Rita (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
This research aims to know the level validation and level practicality of development e-worksheet based on HOTS on doppler effect material from a material expert, media expert, teacher and student. The research type is a 4D model but this research is limited to 3D steps are define, design, and develop due to time and another constraints. The research population was students in SMA Negeri 3 Pematangsiantar Class XI Science. The research population includes trial large group in class XI IPA 1 with 37 students and trial small group with 6 students. The research population has a total of 43 students. The sample research is taken by cluster sampling. In this research, the validators have an instrument with a questionnaire of development e-worksheet to know the level of validation. The instrument of this study was a questionnaire from material expert, media expert, and teacher. The analysis result that development gets level validation and practicality are very worthy with 92,5% from material expert, very worthy with 97,5% from media expert, and very worthy with 95,2% from teacher. Based on the data, the conclusion is that the development of e-worksheet based on HOTS with a 4D model on doppler effect is very worthy of validation and practicality.